A comparison of body image components, including attentional bias and body appraisal, in adolescents with anorexia nervosa or depression, and non-clinical controls - Inken Kirschbaum-Lesch; Anne Radix; Laura Mokros; Anca Sfärlea; Belinda Platt; Gerd Schulte-Körne; Eni S. Becker; Martin Holtmann; Tanja Legenbauer (Child and Adolescent Psychiatry and Mental Health, 2026)
Abstract Background Body image disturbance (BID) is increasingly recognized as a transdiagnostic factor. Beyond its established role in anorexia nervosa (AN), specific components of BID are also associated with the development and maintenance of psychopathology in adolescent Major Depressive Disorder (MDD). However, measurements of different body image components (perceptual, affective, cognitive, and behavioral)—especially objective behavioral measures—remain scarce; the assessment of attentional biases (AB) represents a promising tool to fill this gap. Methods In the present study, two clinical groups of adolescent inpatients (MDD: n = 28; AN: n = 34) and non-clinical controls (NCC: n = 39; aged 13–19 years) completed a body-related Stroop task and a free-viewing task including a body appraisal. Participants also completed questionnaires assessing shape concerns, social appearance anxiety, body checking, avoidance, and reassurance. Results The AN and the NCC groups revealed a significant body-related AB, whereas the MDD group did not. Regarding body appraisal, the clinical groups rated their bodies more negatively than the NCC group. On shape concerns, anxiety, and body avoidance/checking, the AN group showed elevated scores compared to the MDD group. Notably, the NCC only differed significantly from the AN group regarding shape concerns. Conclusions The three groups exhibited distinct BID profiles, identifying pathological body appraisal as a transdiagnostic feature that suggests body dissatisfaction interventions could also mitigate adolescent depressive symptoms. Furthermore, the lack of behavioral differences between healthy adolescents and the AN group underscores the need for early prevention targeting checking and avoidance to prevent the progression into clinical eating disorders.